Yields of multicharged ions scattered and recoiled from a clean silicon surface. - Gauthier, Pierre. (University of Ottawa (Canada), 1994)
This thesis investigates the basic interactions of energetic ions with the top atoms on a clean surface. This information is of relevance to impact collision ion scattering spectroscopy (ICISS) investigations of surface structure. Using a variety of ions with energies in the keV range e.g. C$\rm\sp+,\ N\sp+,\ O\sp+,\ F\sp+,\ Ne\sp+,\ P\sp+,\ S\sp+,\ Cl\sp+$ and Ar$\sp+,$ incident upon a clean amorphous silicon surface, the outgoing particles were found to contain a significant fraction of multiply charged ions. Note that the ejected ions were energy analysed with a cylindrical electrode electrostatic analyser, designed and built by us, which had a sufficiently large solid angle of acceptance so that good energy spectra could be obtained with beam fluxes which did not significantly damage the surface structure. To explain the appearance of these multicharged ions, a charge exchange model is described that considers the interaction domain to be divided into three steps: the incoming trajectory, the close encounter and the outgoing trajectory. A definite threshold distance of closest approach for the production of each of the multicharged ion species was found. These threshold distances directly confirm the model in which multiply charged ions are created in binary encounters by molecular orbital electron promotion, and then are partially neutralized as they leave the surface. The molecular orbital correlation diagram can associate particuliar crossings responsible for each multicharged ion species observed.
Keywords: Physics, Molecular.